2008
DOI: 10.1111/j.1600-6143.2008.02339.x
|View full text |Cite
|
Sign up to set email alerts
|

Health Outcomes for Living Kidney Donors with Isolated Medical Abnormalities: A Systematic Review

Abstract: Individuals with isolated medical abnormalities (IMAs) are undergoing living donor nephrectomy more frequently. Knowledge of health risks for these living donors is important for donor selection, informed consent and follow-up. We systematically reviewed studies with ≥3 living kidney donors with preexisting IMAs, including older age, obesity, hypertension, reduced glomerular filtration rate (GFR), proteinuria, microscopic hematuria and nephrolithiasis. We abstracted data on study and donor characteristics, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 64 publications
1
88
1
1
Order By: Relevance
“…Reduced NO bioavailability, characteristic of endothelial dysfunction, is also widely recognized in hypertensive patients (32). Furthermore, analysis of renal function after kidney donation from hypertensive donors demonstrated a greater increase in serum creatinine in hypertensive donors compared with normotensive donors 6.7 years after donation (36).…”
mentioning
confidence: 99%
“…Reduced NO bioavailability, characteristic of endothelial dysfunction, is also widely recognized in hypertensive patients (32). Furthermore, analysis of renal function after kidney donation from hypertensive donors demonstrated a greater increase in serum creatinine in hypertensive donors compared with normotensive donors 6.7 years after donation (36).…”
mentioning
confidence: 99%
“…Knowledge of health risks for these living donors is important for donor selection, informed consent and follow-up. One systematical review with living kidney donors with preexisting IMA showed perioperative outcomes for donors with and without IMAs were similar (Young A, et al 2008). However, few studies reported longer term rates of hypertension, proteinuria or renal function.…”
Section: Being Donor With Medical Abnormalitymentioning
confidence: 99%
“…[5][6][7][8][9] United Kingdom guidelines support the practice of using otherwise healthy overweight and moderately obese donors (body mass index [BMI] = 25 to 35 kg/m 2 ). Guidelines have been modified recently for very obese status (BMI ≥ 35 kg/m 2 ) from being an absolute contraindication, and very obese potential donors are "discouraged" but not prevented from donating.…”
Section: Safety Of Nephrectomy In Morbidly Obese Donorsmentioning
confidence: 99%